Management of ANC with Oligohydramnios and Uteroplacental Insufficiency- A Case Report - Pragati P. Kamble, Mrs. Arundhatee Gawande, Roshan Umate (Drugs and Cell Therapies in Hematology, 2021)
A low level of amniotic fluid during pregnancy is referred to as oligohydramnios. It's defined by an amniotic fluid index below the 5th centile for the gestational age, and it affects about 4.5 percent of pregnancies to term. During pregnancy, there is insufficient amniotic fluid around your baby in this condition. Only approximately 4% of pregnancies result in this. Amniotic fluid is required for your baby's growth. This is a good example. Oligohydramnios may be idiopathic or have a maternal, fetal, or placental cause. The fetal prognosis depends on several factors, including the underlying cause, the severity (reduced versus no amniotic fluid), and the gestational age at which oligohydramnios occurs. Because an adequate volume of amniotic fluid is critical to normal fetal movement and lung development and uterine compression is cushioned for the foetus and umbilical cord, pregnancies complicated by oligohydramnios from any cause are at risk for fetal deformation, pulmonary hypoplasia, and umbilical cord compression. Presenting complaint and investigations: A 20 year old female was admitted in Acharya Vinoba Bhave Rural Hospital on 02/03/2021with Chief Complaints, Pain in abdomen, low amniotic Fluid, low maternal weight gain, Abdominal Discomfort, sudden drop in fetal heart rate. After physical examination and investigation doctor diagnosis a case of Primigravida 30.2 weeks gestational age with Oligohydramnios and uteroplacental insufficiency. The main diagnoses, therapeutics interventions, and outcomes: A Primi gravida with 30.2 weeks of GA with oligohydramnios and uteroplacental insufficiency. After physical examination and Investigation, doctor was detected A case of Primigravida 30.2 weeks gestational age with Oligohydramnios And utero placental insufficiency With patient was treated analegesic drug to reduce pain. Also provide a arginate sachet and protein powder. Present case was stable but according to ultrasonography findings amniotic fluid index is 7cm. Nursing Perspectives: Administration fluid replacement i.e. DNS and RL. Monitored for fetal heart rate and vital signs checked per hourly. Proper drugs administered to the patient i.e Tab c-tax 200mg BD, tab Pan 40mg bd, tab ecosprin 75mg hs etc given to the patient. Conclusion: Patient was admitted in Acharya Vinoba Bhave Rural Hospital Sawangi(M), Wardha and was diagnosed as oligohydramnios and got appropriate treatment and her condition is improved. Patient delivered by Cesarian section on date 07/05/2021 living female child birth weight of the baby at birth 2.5kg, Apgar score was 9. The baby cried immediately after birth.